Fractional photo-current dependence of graphene quantum dots prepared from carbon nanotubes - Kundu, Sumana; Ghosh, Sujoy; Fralaide, Michael; Narayanan, T. N.; Pillai, Vijayamohanan K.; Talapatra, Saikat (Physical Chemistry Chemical Physics, 2015)
We report on the photo-conductivity studies of chemically synthesized graphene quantum dots (GQDs) of average size 12 nm obtained by the oxidative acid treatment of MWCNTs. The dependence of photocurrent I-ph (I-ph = I-ill - I-dark) on the laser intensity P under a wide range of laser intensities (5 mW <= P <= 60 mW) shows a fractional power dependence of I-ph on light intensity. The temperature dependence (300 K < T < 50 K) of I-ph observed in thin films of these GQDs indicates that in the higher temperature region (T > similar to 100 K), as the temperature increases, the number of thermally generated carriers increase resulting in increased I-ph. At sufficiently low temperatures (T <= 100 K), a constant I-ph is observed, indicating a constant photocarrier density. Such a behavior is typically observed in many photoactive disordered semiconductors, which are often used in a variety of applications. We believe that the investigations presented here will enhance our understanding of the photocurrent generation phenomenon in chemically obtained GQDs.